Impact of weekly iron-folic acid supplementation on nutritional status and parasitic reinfection among school-age children and adolescents in Sub-Saharan Africa: a systematic review and meta-analysis - Kedir, Shemsu; Abate, Kalkidan Hassen; Mohammed, Bekri; Abafita, Jemal; Ademe, Beyene Wondafrash (Frontiers in Pediatrics, 2024)
Background: Two significant etiological factors contributing to iron deficiency anemia, posing substantial public health challenges in sub-Saharan Africa, are soil-transmitted helminths and malaria. This study carried out the effect of weekly iron-folic acid supplementation (WIFAS) on the nutrition and general health of school-age children and adolescents in sub-Saharan Africa, a systematic review and meta-analysis have been conducted.To find pertinent publications for this study, a thorough search was carried out on May 20, 2023, across five databases: Pubmed (MEDLINE), Web of Science, Scopus, Cochrane Library, and Google Scholar. In addition, a search was conducted on August 23, 2023, to capture any new records. The inclusion criteria for the studies were based on school-age children and adolescent populations, randomized controlled trials, and investigations into the effects of WIFAS. The outcomes of interest were measured through anthropometric changes, malaria, and helminthic reinfection.Results: A systematic review of 11 articles revealed that WIFAS significantly decreased the risk of schistosomiasis reinfection by 21% among adolescents (risk ratio = 0.79, 95%CI: 0.66, 0.97; heterogeneity I 2 = 0.00%, P = 0.02). However, no significant impact was observed on the risk of malaria reinfection (risk ratio = 1.02, 95%CI: 0.92, 1.13; heterogeneity I 2 = 0.00%, P = 0.67) or A. Lumbricoides reinfection (risk ratio = 0.95, 95%CI: 0.75, 1.19; heterogeneity I 2 = 0.00%, P = 0.65). Moreover, the analysis demonstrated that there is no significant effect of iron-folic acid supplementation in measured height and height for age Z-score (HAZ) of the school-age children (Hedge's g -0.05, 95%CI: -0.3, 0.2; test for heterogeneity I 2 =0.00%, P =0.7) and (Hedge's g 0.12, 95%CI: -0.13, 0.37; test for heterogeneity I 2 =0.00%, P =0.36) respectively.The effectiveness of WIFAS in reducing the risk of schistosomiasis reinfection in adolescents has been demonstrated to be greater than that of a placebo or no intervention.Additionally, the narrative synthesis of iron-folic acid supplementation has emerged as a potential public health intervention for promoting weight change. Therefore, WIFAS may be implemented as part of a comprehensive public health strategy to address schistosomiasis in adolescents.